2021
DOI: 10.15381/rinvp.v24i1.20132
|View full text |Cite
|
Sign up to set email alerts
|

Empatía y habilidades comunicativas en profesionales de la salud que trabajan con enfermedades crónicas pediátricas

Abstract: Las enfermedades crónicas pediátricas tienen una alta tasa de prevalencia en Argentina, sin embargo, poco se ha estudiado acerca de las competencias profesionales necesarias para la intervención en estos casos, que resultan ser importantes para alcanzar objetivos terapéuticos. El objetivo de este estudio fue indagar la relación entre la empatía y las habilidades comunicativas en profesionales de la salud que trabajan con pacientes pediátricos con enfermedades crónicas. El muestreo fue por conveniencia y compue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…They obtained a medium level of empathy according to the JSE with a score of 118.5 (SD) 14.9 points, while the IRI indicated a low level of empathy with a score of 58.4 ± 9.9 (33). Similarly, Argentinean and foreign HCWs specializing in pediatric chronic diseases demonstrated a medium level of empathy, with a mean score of 82.15 (SD) 7.81 (49). Although years of professional experience do not significantly correlate with overall empathy levels, it was observed that individuals with less than 10 years of experience tend to exhibit a greater capacity for understanding another person's perspective.…”
Section: Overall Empathy Analysismentioning
confidence: 92%
“…They obtained a medium level of empathy according to the JSE with a score of 118.5 (SD) 14.9 points, while the IRI indicated a low level of empathy with a score of 58.4 ± 9.9 (33). Similarly, Argentinean and foreign HCWs specializing in pediatric chronic diseases demonstrated a medium level of empathy, with a mean score of 82.15 (SD) 7.81 (49). Although years of professional experience do not significantly correlate with overall empathy levels, it was observed that individuals with less than 10 years of experience tend to exhibit a greater capacity for understanding another person's perspective.…”
Section: Overall Empathy Analysismentioning
confidence: 92%
“…prevenir, están muy relacionadas con su calidad en la comunicación que establece. Raba et al (28) considera que las habilidades comunicativas en la relación médico paciente, influyen en mejores resultados en la salud física, mental, funcional y subjetiva, en el nivel de satisfacción de pacientes y familiares, en el cumplimiento de los tratamientos, en la eficiencia clínica y en la disminución del número de complementarios. La relación médico-paciente es una particularidad dentro de las relaciones interpersonales.…”
Section: Relación Entre La Calidad De La Atención Y La Comunicaciónunclassified